TIMING GRACE: REFLECTIONS ON THE TEMPORALITY OF PREACHING (Acta Theologica)
A review on Cilliers, J., (AFRICAN SUN MeDIA, SUN PReSS, 2019), 246 pp. Price: R250 (hardcopy); R280 (e-book) ISBN: 978-1-928480-22-8 & 978-1- 928480-23-5, (E-book). www.africansunmedia.co.za/ orders@africasunmedia.co.za/021 201 0071